Changes in the Spleen During Hepatitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article discusses the morphological changes in the spleen of children under the age of 18 with toxic hepatitis. The research results confirm the active involvement of the spleen in the pathogenesis of toxic hepatitis. Early detection of these changes is important for assessing disease severity and planning treatment strategies. Further, more extensive studies are recommended in the future.